Epilithic Periphyton and Detritus Ecology of the Spring-fed Stream Eastern Nayar in Garhwal Himalaya - V. P. Balodi; Anoop K. Dobriyal; W. K. Joshi; S. P. Uniyal; Anju Thapliyal (Environment Conservation Journal, 2004)
The paper deals with the study of epilithic periphyton and detritus standing stock in the river Eastern Nayar, which forms an important part of the food for macrozoobenthos and the fish, thus contributing greatly to the productivity of the stream.